Georgia Architectural and Historic Properties Survey of 806 1/2 Nardo St., Valdosta, Ga., December 1980 - Smith, Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of 806 1/2 Nardo St., Valdosta, Ga., December 1980. One story rectangular plan house with gabled roof. Clapboard siding. Gabled porch, exposed rafters. Double hung sash windows with 1/1 lights. Set on brick piers. Poor condition. Date of Construction: App. 1910-1915. Typical vernacular house; part of a district which could have possibly developed as housing for millworkers at the Valdosta Mill Company in the early 1900's. Not significant in terms of a N.R. district. Too many modern buildings in the area.
Georgia Architectural and Historic Properties Survey of 806 1/2 Nardo St., Valdosta, Ga., December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 3 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 81.3 MB (85,314,812 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Valdosta (Ga.)